Minimally invasive restorative treatment with direct composite veneers: Case report - Apostolska Sonja; Rendžova Vasilka; Eftimoska Marina; Filipovska Vesna; Elenčevski Sašo; Janeva Nadica (Serbian Medical Society - Dental Section, Belgrade, 2017)
Esthetic and minimally invasive restorative techniques are current topics in dentistry. Introduction of modern composite materials and adhesive technology provided numerous options for design of esthetic restorations without invasive teeth preparation common for traditional prostodontic restorations. Modern esthetic dentistry can provide solutions for simple as well as complex cases by implementation of various alternatives.